FACTORS ASSOCIATED WITH SIBLING RIVALRY IN THE WORKING AREA OF PUSKESMAS BLANG BINTANG - Intan Permata Sari; Yusnaini; Kartinazahri (Department of Midwifery, Health Polytechnic of Aceh, 2022)
Introduction: Sibling rivalry is a competition that occurs between siblings. Sibling rivalry usually occurs in childhoodwhen the age difference between siblings is too close, commonly at the age range of 3-5 years (preschool), and willreappear when the age of 8-12 years (school age). Sibling rivalry usually increases in preschoolers (3-5 years). Siblingrivalry is usually caused by children who feel they have lost their parents' love and regard their siblings as rivals ingetting love from their parents and the parent’s comparison between siblings.Methods: This study was descriptive-analytic observational with a cross-sectional approach. As the multistage samplingtechnique was used which consisted of purposive sampling as the first stage, stratified random sampling as the secondstage, and simple random sampling as the third stage. The sample size of the study was 154 toddlers. Univariate analysisand bivariate analysis were performed using Chi-Square Test (x ) with a 95% confidence interval.Result: Sibling rivalry mainly occurs in the eldest child, toddlers, male children, and the mother's lack of knowledge anddemocratic parenting.Conclusion: There was an association between birth order, child’s age, gender, mother’s knowledge, and parenting stylewith sibling rivalry in children.